Halal Social Marketing: Building Attitude Toward Halal Portrayals Through Media Exposure - Gabriella, Joelle; Sudiani, I Gusti Made Ayu (Ilomata International Journal of Social Science, 2025)
Introduction: This paper explores how halal advertising exposure influences consumer perceptions—specifically perceived authenticity, congruence, and trustworthiness—mediated by attitude toward halal portrayal. The research is grounded in Indonesia's booming halal cosmetics industry, with Wardah as a case study representing strategic halal social marketing. Amid increasing consumer demand for faith-aligned branding, the study addresses a key research question: Does halal advertising exposure directly affect consumer perception, or is this relationship mediated by attitudes toward religious portrayals in media?. Novelty: The novelty of this study lies in its proposition that advertising does not shape consumer perception through direct exposure alone but through the evaluative lens of portrayal attitude—an insight underexplored in prior literature. By integrating the Stimulus–Organism–Response (SOR) framework within a religious branding context, this research offers a unique contribution to both advertising theory and halal consumer behaviour studies. Methods: Using a quantitative, cross-sectional design, data were collected from 259 Muslim female consumers in Jakarta who have engaged with Wardah’s halal advertising. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to test the relationships and mediation effects within the model. Results: The results indicate that halal advertising directly influences perceived congruence and trustworthiness, but not authenticity. Attitude toward portrayal fully mediates the effect on perceived authenticity and partially mediates the other two outcomes. These findings highlight the critical role of attitudinal processing in translating religious advertising into meaningful brand evaluations. Conclusion: This study concludes that effective halal advertising must go beyond certification, embedding identity-based storytelling and cultural relevance to foster trust and perception. Strategically portraying Islamic values is not only an ethical imperative but a persuasive tool in resonating with modern Muslim consumers.